Infectious Patterns (Palíndromo, 2021)
The joy, pleasure and fun of writing as tools of affective direction. Short essay with words and drawings, that answers the question "how do you amplify yourself?", proposed by the Contágio 3x3 Residency (April 2017, Sesc Pinheiros).
Keywords: Writing; Pleasure; Affective direction